2015
DOI: 10.1186/1471-2261-15-3
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Tako-Tsubo cardiomyopathy (TTC) in a pre-menopausal woman: late sequelae of a traumatic event?

Abstract: Background“Tako-Tsubo cardiomyopathy” (TTC) is a syndrome characterized by left ventricular (LV) wall motion abnormalities, usually without coronary artery disease, mimicking the diagnosis of acute coronary syndrome. It most often affects post-menopausal women and TTC tends to run a benign course with very low rates of recurrence, complications or mortality. The condition is also called “stress-induced cardiomyopathy” because acute physical or emotional stress appears to be frequently related to its onset. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…No emotional stress, normal cardiac enzyme values and a normal ECG ST-segment were important diagnostic clues of diverticulum in this case. In a characteristic takotsubo ventricle, the base of the left ventricle is hyperkinetic while the remainder of the left ventricle is akinetic or dyskinetic [ 10 , 11 ]. However, the echocardiograph of this patient showed normal ventricular function and wall motions, and the apical protrusion was contractile.…”
Section: Discussionmentioning
confidence: 99%
“…No emotional stress, normal cardiac enzyme values and a normal ECG ST-segment were important diagnostic clues of diverticulum in this case. In a characteristic takotsubo ventricle, the base of the left ventricle is hyperkinetic while the remainder of the left ventricle is akinetic or dyskinetic [ 10 , 11 ]. However, the echocardiograph of this patient showed normal ventricular function and wall motions, and the apical protrusion was contractile.…”
Section: Discussionmentioning
confidence: 99%
“…The use of vasopressors is frequently applied to counterbalance anaesthesia-induced hypotension 1. Hefner et al reported a case of premenopausal women with fourfold TCM related to chronic term post-traumatic distress, triggered by previous miscarriage 2. The common denominator with our case is distress related to pregnancy loss.…”
Section: Descriptionmentioning
confidence: 60%
“…TTC may be precipitated by eclampsia during pregnancy [21]. Rarely, TTC may have the tendency to be recurrent [22]. TTC is responsible for 1.2-2.2% of total hospital admissions for suspected acute coronary syndrome [23;24].…”
Section: Discussionmentioning
confidence: 99%